Growth and yield performances of (Abelmoschus esculentus) inoculated with different concentration of IMO / Nur Suraya Abdullah …[et al.] - Abdullah, Nur Suraya; Wan Zulkifli, Wan Muhamad Syafiq; Abdul Aziz, Noorshilawati; Yusop, Mohamad Amir Shah; Mohammed, Anisah; Rosli, Fazidah (2013)
The existence of awareness on negative effect of using inorganic fertilizer to human health and environment resulted the farmers shift to the use of organic fertilizer and focused on organic farming. Organic farming involves the use of natural resources derived from agricultural waste as a source of fertilizer and pesticide. An experiment was conducted to study the effect of different concentrations of indigenous microorganism on growth and yield of okra (Abelmoschus esculentus). The results of the study indicated that inoculation with 5% concentrations of indigenous microorganism significantly enhanced the yield (10%), plant height (12.4%), leaves number (15.8%), fresh weight (150%) and dry weight (69.2%) of okra. These properties showed the benefits of indigenous microorganism in promoting soil fertility and then can increased growth and yield of crop production.